Formal education, mismatch and wages after transition: Assessing the impact of unobserved heterogeneity using matching estimators - Ana Lamo; Julián Messina (Institute for the Study of Labor (IZA), 2010)
This paper studies the incidence and consequences of the mismatch between formal education and the educational requirements of jobs in Estonia during the years 1997-2003. We find large wage penalties associated with the phenomenon of educational mismatch. Moreover, the incidence and wage penalty of mismatches increase with age. This suggests that structural educational mismatches can occur after fast transition periods. Our results are robust for various methodologies, and more importantly regarding departures from the exogeneity assumptions inherent in the matching estimators used in our analysis.
Keywords: J0; 330; Education mismatch; wage determination; matching estimators; Qualifikation; Bildungsniveau; Anforderungsprofil; Matching; Lohnbildung; Übergangswirtschaft; Estland